2016
DOI: 10.1186/s12967-016-0947-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of atherosclerosis as detected by coronary artery calcium and carotid intima-media thickness reveals significant atherosclerosis in a cross-sectional study of psoriasis patients in a tertiary care center

Abstract: BackgroundPsoriasis is a chronic inflammatory disease of the skin and joints that may also have systemic inflammatory effects, including the development of cardiovascular disease (CVD). Multiple epidemiologic studies have demonstrated increased rates of CVD in psoriasis patients, although a causal link has not been established. A growing body of evidence suggests that sub-clinical systemic inflammation may develop in psoriasis patients, even from a young age. We aimed to evaluate the prevalence of atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
0
27
0
1
Order By: Relevance
“…The increased risk of ischaemic heart disease and cerebrovascular disease in patients with concurrent psoriasis and depression may be due to the systemic inflammatory nature of these two diseases, which may incrementally promote atherosclerosis development . Prior studies have demonstrated an increased degree of aortic vascular inflammation, coronary artery atherosclerosis and carotid artery atherosclerosis in psoriasis patients compared with healthy controls . Similarly, the prevalence and severity of atherosclerosis is known to be greater in patients with depression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk of ischaemic heart disease and cerebrovascular disease in patients with concurrent psoriasis and depression may be due to the systemic inflammatory nature of these two diseases, which may incrementally promote atherosclerosis development . Prior studies have demonstrated an increased degree of aortic vascular inflammation, coronary artery atherosclerosis and carotid artery atherosclerosis in psoriasis patients compared with healthy controls . Similarly, the prevalence and severity of atherosclerosis is known to be greater in patients with depression .…”
Section: Discussionmentioning
confidence: 99%
“…11 Prior studies have demonstrated an increased degree of aortic vascular inflammation, 31,32 coronary artery atherosclerosis 33,34 and carotid artery atherosclerosis in psoriasis patients compared with healthy controls. 35,36 Similarly, the Psoriasis, depression and cardiovascular diseases prevalence and severity of atherosclerosis is known to be greater in patients with depression. [37][38][39][40][41] Therefore, the combined impact of psoriasis and depression on atherosclerosis development may contribute to the higher vascular risk in patients with both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Medical comorbidities do not only comprise cardiovascular diseases (Santilli et al, ). They range from autoimmunity disorders (Della Valle et al, ; Fiore, Leone, Maraolo, Berti, & Damiani, ; Watad et al, ) to respiratory ones (Confalonieri et al, ; Damiani, Radaeli, Olivini, Calvara‐Pinton, & Malerba, ; Malerba et al, ; Santus et al, ) and were computed to have contributed to the economic burden of psoriasis with $36.4 billion.…”
Section: The Epidemiological and Societal Burden Of Psoriasismentioning
confidence: 99%
“…Medical comorbidities do not only comprise cardiovascular diseases (Santilli et al, 2016). They range from autoimmunity disorders (Della Valle et al, 2018;Fiore, Leone, Maraolo, Berti, & Damiani, 2018;Watad et al, 2019) to respiratory ones (Confalonieri et al,in Sweden (€11,928), based also on treatment type.…”
Section: The Epidemiological and Societal Burden Of Psoriasismentioning
confidence: 99%
“…This explains the several comorbidities that frequently present in patients with psoriasis. [2][3][4] The pathomechanism involves a complex interaction of inflammatory chemokines, with a predominantly T-helper 17 profile, that have been shown to be elevated in serum and skin. 1,5 Conflicting results have been reported regarding clinical uses for proinflammatory biomarkers, such as correlation with clinical severity and prediction of therapeutic response.…”
Section: Tissue Inflammatory Biomarkers In Chronic Plaque Psoriasis: mentioning
confidence: 99%